Syphilis Self-testing: A Nationwide Pragmatic Study Among Men Who Have Sex With Men in China - Wang, Cheng (Clin Infect Dis, 2020)
BACKGROUND: Syphilis self-testing may help expand syphilis testing among men who have sex with men (MSM). China has rapidly scaled up human immunodeficiency virus (HIV) self-testing, creating an opportunity for integrated syphilis self-testing. However, there is a limited literature on implementing syphilis self-testing. METHODS: A cross-sectional online survey was conducted among Chinese MSM in 2018. Participants completed a survey instrument including sociodemographic characteristics, sexual behaviors, syphilis self-testing, and HIV self-testing history. Multivariable logistic regression was conducted to identify correlates of syphilis self-testing. We also recorded potential harms associated with syphilis self-testing. RESULTS: Six hundred ninety-nine MSM from 89 cities in 21 provinces in China completed the study. A total of 361/699 (51.7%) men tested for syphilis, of whom 174/699 (24.9%) men used syphilis self-testing. Among 174 who had self-tested, 90 (51.7%) reported that the self-test was their first syphilis test and 161 (92.5%) reported that they undertook syphilis self-testing together with HIV self-testing. After adjusting for covariates, syphilis self-testing was correlated with disclosure of sexual orientation to family or friends (adjusted odds ratio [aOR], 1.90; 95% confidence interval [CI], 1.32–2.73), reporting 2–5 male sexual partners (aOR, 1.81; 95% CI, 1.04–3.16), HIV self-testing (aOR, 39.90; 95% CI, 17.00–93.61), and never tested for syphilis in the hospital (aOR, 2.96; 95% CI, 1.86–4.72). Self-reported harms associated with syphilis self-testing were minimal. CONCLUSIONS: Scaling up syphilis self-testing could complement facility-based testing in China among MSM. Self-testing may increase first-time testing and has limited harms. Our findings suggest that syphilis self-testing could be integrated into HIV self-testing services.